2018
DOI: 10.1021/acsbiomaterials.8b00858
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Delivery with Stem Cell Membrane-Coated Magnetic Nanoparticles for Imaging-Guided Photothermal Therapy and Gene Therapy

Abstract: Biomimetic cell membrane coated nanoparticles (NPs) with desirable features have been extensively applied for various personalized biomedicine. However, there have not been relative explorations by employing the membrane nanocomplexes for small interfering RNA (siRNA) delivery. Herein, Fe 3 O 4 @PDA NPs with good photothermal capability were applied for efficient siRNA loading and delivery, which were then coated by mesenchymal stem cells (MSCs) to form a membrane. The data showed that MSCs membrane coated Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 31 publications
(52 reference statements)
1
68
0
Order By: Relevance
“…Both in vivo and in vitro results, supported the excellent inhibitory effect on 4T1 tumor growth of the anti-survivin siRNA-loaded M-PLL. In a different approach, Mu et al developed a cell membrane-coated PDA nanocarrier for enhanced target precision and siRNA delivery at tumor sites, coupled with imagine guided therapy [ 203 ]. The complex nanodrug, namely Fe 3 O 4 @PDA−siRNA@MSCs, consisted of an internal iron oxide-PDA core on which siRNA were bound to the PDA layer through π-π stacking and an external mesenchymal stem cells (MSCs) membrane vesicle coating.…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…Both in vivo and in vitro results, supported the excellent inhibitory effect on 4T1 tumor growth of the anti-survivin siRNA-loaded M-PLL. In a different approach, Mu et al developed a cell membrane-coated PDA nanocarrier for enhanced target precision and siRNA delivery at tumor sites, coupled with imagine guided therapy [ 203 ]. The complex nanodrug, namely Fe 3 O 4 @PDA−siRNA@MSCs, consisted of an internal iron oxide-PDA core on which siRNA were bound to the PDA layer through π-π stacking and an external mesenchymal stem cells (MSCs) membrane vesicle coating.…”
Section: Mnp Based Therapy and Theranosticsmentioning
confidence: 99%
“…A co-extrusion method 18 with slight modifications was used to synthesize DOX-SPIO@MSCs. MSVs (prepared as described above) were co-extruded with DOX-SPIO through a 200 nm polycarbonate porous membrane 10 times.…”
Section: Synthesis Of Dox-spio@mscsmentioning
confidence: 99%
“…Likewise, mesenchymal stem cell (MSC) membrane‐derived vesicles, with long circulation times and good tumor targeting properties, were studied to camouflage polydopamine (PDA)‐coated hydrophobic Fe 3 O 4 NPs, as an image‐guided photothermal and siRNA delivery platform. The experimental results showed that the Fe 3 O 4 @PDA‐siRNA@MSCs NPs displayed good MSC‐mimicking ability for tumor targeting, photothermal conversion efficiency, allowed MR imaging, and also silenced the target gene in a DU145 xenograft mouse model 302…”
Section: Challenges and Future Directionsmentioning
confidence: 99%